A tortura como trauma individual e social : vivências do período civil-militar (1964-1895) - Vieira, Renan Martimiano (2014)
The objective of this study is to investigate trauma in tortured individuals - in the context of the military dictatorship in Brazil - using autobiographical narratives by victims after having experienced the trauma. Psychoanalysis is our theoretical, specifically the General Theory of Seduction (GTS). Two were the works we selected as material for our analyses: Retrato Calado, by Luiz Roberto Salinas Fortes and Memórias do Esquecimento by Flávio Tavares, the general analysis was inspired in Fernandes thesis (2008). Our starting point is the theoretical proposition of the GTS regarding the original trauma that treats the constitution of psyche as an essentially traumatic event (Laplanche, 1987/1992). The narrative analyses seek to answer the following questions: Among the elements present in what Laplanche called Fundamental Anthropological Situation (FAS) regarding the encounter of the adult and the newborn child, what could benefit our understanding on the trauma caused by torture? What would be the characteristics of the message present in torture and the possible consequences? How could the written testimonial narratives benefit trauma elaboration? Our initial hypothesis is that torture renews FAS characteristic elements but featuring sender's messages that are mostly experienced as the receiver's intrusion, which results from a particularly violent scenario. These messages relate to the notion of unconscious jammed, which is the depository psychic instance of the messages that have not passed through the filter of translation precisely because they have been meddling with violence. Another hypothesis that we expose here is that the narratives of testimony, written or told by torture survivors, may start the first translations of these intrusive messages. Our research enabled us to make a few considerations on trauma caused by torture regarding its sexual, disruptive nature; the victim's impotence facing the trauma and the torture scenario; finally, we propose a mechanism to benefit trauma elaboration consisting in an inner attitude of self-interrogation by the victim.